ANALISIS STRATEGI PERSAINGAN BANK UMUM DALAM PASAR KREDIT MIKRO DAN KECIL DI EKS-KARESIDENAN BESUKI (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2011)
Banking is one of the financial institutions that provide financial services to the society. Indonesian monetary policies support small and micro lending of commercial banks as primary function in intermediary institution. Commercial banks have a strategy to response the internal and external environment in credit market. This study aims to determine strategies of commercial banks for competition in the micro and small credit market in Eks-Karesidenan Besuki. The study area includes all regency of Eks-Karesidenan Besuki like Jember, Bondowoso, Situbondo and Banyuwangi. This study using primary data from key-informants. Key informant selected by snow ball method . The technique of collecting data using questionnaires and in-depth interview. Research analysis using the Analysis Hierarchy Process (AHP) and descriptive analysis. The results showed that the commercial banks have a major strategy in the micro and small credit markets in Eks-Karesidenan Besuki through marketing strategies. The Dominate of marketing strategies commercial banks in micro dan small credit market is credit limit strategy, interest rate and term of loan.